Transformation Of Political Marketing Practices - Riki Mirzam; Prahastiwi Prahastiwi; Julius Slamet (International Journal Labs, 2024)
Political marketing is one of the fields of communication that is still relatively new compared to other fields of communication, in political marketing there have been many discussions about political campaign strategies but not many have discussed changes in strategies from time to time. The purpose of this study is to provide insight into changes in political marketing practices over time. The method used is a qualitative research method of literature review, from this research there are five transformations of political marketing practices, namely direct political marketing, mass media political marketing, digital political marketing, social media political marketing, political marketing using buzzers. The conclusion of this study is that there are five political marketing strategies that can be used but must consider the advantages and disadvantages. There are still limitations to this researcher because it is still discussed in general and in the future it can be continued to discuss more specifically in each strategic area of political distribution.